Movements on the Portuguese-Spanish border and diplomatic correspondence in the Spanish Civil War - Sousa, Pedro Sobral de (Hispania Nova, 2022)
In the matter of the Spanish Civil War, the July 1936 coup d'état aimed to overthrow the Spanish Republican Government. This act generated a civil war that lasted three years and had major implications for Portugal. Portugal had an authoritarian government led by Oliveira Salazar. The interests of the Portuguese government were contrary to those of the Spanish republican government. Thus, the coup d'état was the opportunity desired by Portugal to support a possible government with identical interests in the neighboring country. It was a priority to be aware of the movements in the border areas, because on the one hand, it was a place that could be used to support the faction opposed to the Republican Government and, on the other hand, it was an area that should be controlled to prevent the entry of elements. destabilizers in Portugal. However, it was difficult to obtain reliable and detailed information about events in the border areas. The distance from Lisbon and the extension of the border made it difficult. This article explores an important source of information and local knowledge about the border area, through Portuguese diplomatic correspondence. Particular emphasis is given to the movement of materials and people, as well as reports of possible dangers reported by diplomats.
Keywords: Spanish Civil War; refugees; Estado Novo; diplomacy